Simulation of High Impact Rainfall Events Over Southeastern Hilly Region of Bangladesh Using MM5 Model. (29th December 2013) - Ahasan, M. N.; Chowdhury, M. A. M.; Quadir, D. A.
Abstract : Simulation of high impact rainfall events over southeastern hilly region of Bangladesh has been carried out using Fifth-Generation PSU/NCAR Mesoscale Model (MM5) conducting two historical rainfall events, namely, 21 June, 2004 and 11 July, 2004. These extraordinary rainfall events were localized over the Rangamati region and recorded 304 mm and 337 mm rainfall on 21 June, 2004 and 11 July, 2004, respectively, over Rangamati within a span of 24 h. The model performance was evaluated by examining the different predicted and derived parameters. It is found that the seasonal monsoon trough has northerly position compared to normal and pass through Bangladesh extending up to northeast India for both cases. The heat low was found to be intense (996 hPa) with strong north-south pressure gradient (12–15 hPa). The analysis of the geopotential height field at 200 hPa shows that the Tibetan high is shifted towards south by 7-8° latitudes with axis along 22–25°N for both cases. The analysis of the wind field shows that the areas of high impact rainfall exhibit strong convergence of low level monsoon circulation (~ 19–58 knots). The strong southwesterlies were found to exist up to 500 hPa level in both cases. The lower troposphere (925–500 hPa) was characterized by the strong vertical wind shear (~ 9–18 ms −1 ) and high relative vorticity (~ 20–40 × 10 −5  s −1 ). The analysis also shows that the areas of high impact rainfall events and neighbourhoods are characterized by strong low level convergence and upper level divergence. The strong southwesterly flow causes transportation of large amount of moisture from the Bay of Bengal towards Bangladesh, especially over the areas of Rangamati and neighbourhoods. The high percentage of relative humidity extends up to the upper troposphere along a narrow vertical column. Model produced details structure of the spatial patterns of rainfall over Bangladesh reasonably well though there are some biases in the rainfall pattern. The model suggests that the highly localized high impact rainfall was the result of an interaction of the mesoscale severe convective processes with the large scale active monsoon system.